2020
DOI: 10.1242/dmm.041962
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specific and athero-protective roles for RIPK3 in a murine model of atherosclerosis

Abstract: Receptor-interacting protein kinase 3 (RIPK3) was recently implicated in promoting atherosclerosis progression through a proposed role in macrophage necroptosis. However, RIPK3 has been connected to numerous other cellular pathways, which raises questions about its actual role in atherosclerosis. Furthermore, RIPK3 is expressed in a multitude of cell types, suggesting that it may be physiologically relevant to more than just macrophages in atherosclerosis. In this study, Ripk3 was deleted in macrophages, endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…Here we sought to complement these studies by providing new insights into Ripk3 transcriptional regulators. We designed our study to identify such regulators in ECs because our previous research indicates that endothelial RIPK3 expression levels impact vascular stability, angiogenesis, and anti-inflammatory properties [10][11][12]. Therefore, we reasoned that elucidation of transcriptional regulators of endothelial Ripk3 could provide new therapeutic targets for modulating vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we sought to complement these studies by providing new insights into Ripk3 transcriptional regulators. We designed our study to identify such regulators in ECs because our previous research indicates that endothelial RIPK3 expression levels impact vascular stability, angiogenesis, and anti-inflammatory properties [10][11][12]. Therefore, we reasoned that elucidation of transcriptional regulators of endothelial Ripk3 could provide new therapeutic targets for modulating vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this RIPK3-mediated vascular rupture is not obviously linked to EC necroptosis or inflammation, indicating that aberrant RIPK3 expression can contribute to other damaging processes in ECs. Conversely, genetic deletion of endothelial Ripk3 impairs developmental angiogenesis [ 11 ] and exacerbates vascular lesion formation in a murine atherosclerosis model [ 12 ]. Therefore, endothelial RIPK3 expression must be tightly regulated to maintain vascular integrity, function, and homeostasis at different stages of life.…”
Section: Introductionmentioning
confidence: 99%
“…However, this interpretation, according to which necroptosis induces calcification and has harmful effects only in atherosclerosis, might be oversimplistic. Indeed, specific Ripk3 deletion in macrophages or endothelial cells protects ApoE –/– mice from lipid accumulation, suggesting that necroptosis impacts plaque development differently depending on the cell lineage in which it takes place ( Colijn et al, 2020 ). Moreover, a recent study surprisingly showed that, while inhibition of MLKL expression in ApoE –/– mice predictably impaired necroptosis, it increased lipid accumulation within the plaques ( Rasheed et al, 2020 ).…”
Section: Arguments Against the Phenotypic Change Hypothesismentioning
confidence: 99%
“…However, to Sarah's great surprise, she found that inhibition of RIPK3 in certain cell types has unexpected and pro-atherogenic effects, indicating that it is a poor target for drug design. In particular, deletion of RIPK3 in either macrophages or endothelial cells revealed that RIPK3 has an athero-protective role in these cell types ( Colijn et al, 2020b ). Sarah's work challenges research regarding atherosclerosis and necroptosis to rethink the role of RIPK3 and to acknowledge that it can function in a non-pathological way; she and her colleagues suspect that RIPK3 functions in a multitude of pathways that have very little to do with necroptosis.…”
Section: Outstanding Contributionmentioning
confidence: 99%
“… ABSTRACT Disease Models & Mechanisms (DMM) is delighted to announce that the winner of the DMM Prize 2020 is Sarah Colijn, for her paper entitled ‘Cell-specific and athero-protective roles for RIPK3 in a murine model of atherosclerosis’ ( Colijn et al, 2020b ). The prize of $1000 is awarded to the first author of the paper that is judged by the journal's editors to be the most outstanding contribution to the journal that year.…”
mentioning
confidence: 99%